2017
DOI: 10.1007/s11547-017-0748-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the influence of patient positioning on the reliability of lateral cephalometry

Abstract: Two-dimensional cephalometry is widely used for monitoring orthodontic treatments and for quantifying the outcome of maxillofacial surgery. Despite careful use of a cephalostat, successive radiographs might differ due to slight differences in patient posture. This study evaluates the reliability of lateral cephalometric measurements and estimates the impact of patient positioning on this reliability. We studied cephalograms of 104 patients; 31 of them had two radiographs because the first was deemed unsuitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Cephalometry is a method for standardizing the cephalometric head film, introduced by Broadbent in 1931 23 , and to date has been commonly used as one of the routine examinations in orthodontic diagnoses, prior to starting orthodontic treatment. Cephalometric radiographs have been shown to yield highly reproducible data in many orthodontic studies 24 26 . Since both the source-to-subject and subject-to-film distances are always fixed, it is possible to calculate the magnification of the subject projected on the film in a precise manner 27 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cephalometry is a method for standardizing the cephalometric head film, introduced by Broadbent in 1931 23 , and to date has been commonly used as one of the routine examinations in orthodontic diagnoses, prior to starting orthodontic treatment. Cephalometric radiographs have been shown to yield highly reproducible data in many orthodontic studies 24 26 . Since both the source-to-subject and subject-to-film distances are always fixed, it is possible to calculate the magnification of the subject projected on the film in a precise manner 27 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses were performed to determine possible correlations among groups. All areas were randomly re-measured and errors were calculated by Dahlberg’s formula 24 ; on average, the method error was 1.4 mm 2 (1.4 mm 2 for the Ad, 1.9 mm 2 for the Np, 0.7 mm 2 for the Tn, and 1.6 mm 2 for the Op). Inter-group comparisons were carried out using one-way analysis of variance and chi-square test.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous cross-sectional study, we determined the average Ad/nasopharynx (Np) and Tn/oropharynx (Op) ratios in Japanese children and teenagers. We performed cephalometric analysis, a highly reproducible examination that is routinely performed in orthodontic assessments 15 17 . The present study aimed to construct growth curves for the Ad and Tn, compare these growth curves, and provide a method to assist physicians in deciding whether to perform adenotonsillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…At present, carpal roentgens are regarded as the gold standard to assess bone maturation 9 . In fact, there are several reports on the correlation between the ages determined using carpal bones and the cervical spine 10,[15][16][17] , while the British Orthodontic Society stated that there are uncertainty using carpal radiography in predicting patient's adolescent growth spurt 17 . Lateral cephalometric radiographs are indispensable for clinical orthodontic treatment planning and are often taken at the time of the first visit.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was suggested that it is desirable to initiate treatment during CVMS III in men when inducement of mandibular growth is needed. In addition, mandibular prognathism during the growth period may be managed by a combination of orthodontic and surgical treatment when mandibular growth is remarkable 17,25 . Previous reports have indicated that controlling mandibular growth with functional orthopedic appliance devices is effective in growing patients with skeletal discrepancy 26 .…”
Section: Discussionmentioning
confidence: 99%